TET2 Function in Hematopoietic Malignancies, Immune Regulation, and DNA Repair - Feng, Yimei; Li, Xiaoping; Cassady, Kaniel; Zou, Zhongmin; Zhang, Xi (Frontiers in Oncology, 2019)
Over the last decade, investigation of Ten-Eleven Translocation 2 (TET2) gene function and TET2 mutation have become of increasing interest in the field of hematology. This heightened interest was sparked by the seminal discoveries that 1) TET2 mutation is associated with development of hematological malignancies and that 2) the TET family of proteins is critical in promoting DNA demethylation and immune homeostasis. Since then, additional studies have begun to unravel the question “Does TET2 have additional biological functions in the regulation of hematopoiesis?” Here, we present a mini-review focused on the current understanding of TET2 in hematopoiesis, hematological malignancies and immune regulation. Importantly, we highlight the critical function that TET2 facilitates in maintaining the stability of the genome. Based on our review of the literature, we provide a new hypothesis that loss of TET2 may lead to dysregulation of the DNA repair response, augment genome instability, and subsequently sensitize myeloid leukemia cells to PARP inhibitor treatment.